Proteomic Analysis of Membrane Blebs of Brucella abortus 2308 and RB51 and Their Evaluation as an Acellular Vaccine - Araiza-Villanueva, Minerva; Avila-Calderón, Eric Daniel; Flores-Romo, Leopoldo; Calderón-Amador, Juana; Sriranganathan, Nammalwar; Qublan, Hamzeh Al; Witonsky, Sharon; Aguilera-Arreola, Ma. Guadalupe; Ruiz-Palma, María del Socorro; Ruiz, Enrico A.; Suárez-Güemes, Francisco; Gómez-Lunar, Zulema; et al. (Frontiers in Microbiology, 2019)
Membrane blebs are released from Gram-negative bacteria, however, little is known about Brucella blebs. This work pursued two objectives, the first was to determine and identify the proteins in the membrane blebs by proteomics and in silico analysis. The second aim was to evaluate the use of membrane blebs of Brucella abortus 2308 and B. abortus RB51 as an acellular vaccine in vivo and in vitro. To achieve these aims, membrane blebs from B. abortus 2308 and RB51 were obtained and then analyzed by liquid chromatography coupled to mass spectrometry. Brucella membrane blebs were used as a “vaccine” to induce an immune response in BALB/c mice, using the strain B. abortus RB51 as a positive vaccine control. After subsequent challenge with B. abortus 2308, CFUs in spleens were determined; and immunoglobulins IgG1 and IgG2a were measured in murine serum by ELISA. Also, activation and costimulatory molecules induced by membrane blebs were analyzed in splenocytes by flow cytometry. 228 proteins were identified in 2308 membrane blebs and 171 in RB51 blebs, some of them are well-known Brucella immunogens such as SodC, Omp2b, Omp2a, Omp10, Omp16, and Omp19. Mice immunized with membrane blebs from rough or smooth B. abortus induced similar protective immune responses as well as the vaccine B. abortus RB51 after the challenge with virulent strain B. abortus 2308 (P<0.05). The levels of IgG2a in mice vaccinated with 2308 membrane blebs were higher than those vaccinated with RB51 membrane blebs or B. abortus RB51 post-boosting. Moreover, mice immunized with 2308 blebs increased the percentage of activated B cells (CD19+CD69+) in vitro. Therefore, membrane blebs are potential candidates for the development of an acellular vaccine against brucellosis, especially those derived from the rough strains so that serological diagnostic is not affected.